La competitividad de las artesanías de la zona lacustre del estado de Michoacán - Arreaga Velasco, Rocío Yunuen (Universidad Michoacana de San Nicolás de Hidalgo, 2023)
In Mexico, craft activity is predominantly made up of family businesses that have been producing and selling these products for several years. An important feature of the handicraft activity is that, by focusing only on the elaboration of these products, a large part of the artisans does not visualize the potential that these products have for commercialization through their export to other markets. In this sense, the objective of this research is to know the determinants of the propensity to export of the artisans of the lake zone of the state of Michoacán, identifying the innovation in products, processes or marketing, the affiliation to some public or private organization that promotes artisan development, the intention of the artisans to position themselves in new markets and their own, public/private or family financing for the development of handicraft activities as variables that positively influence the propensity to export handicraft products by the handicraft production units of the Michoacán state zone. To achieve this objective, 329 surveys were applied among the artisans of the lake zone of the state of Michoacán. This information was the basis for estimating a Logit-type econometric model, finding that the variables that have a preponderant positive effect on the propensity to export handicrafts are innovation, the intention of artisans to position themselves in new markets and their own financing for the development of handicraft activities, finding a lesser effect on the affiliation of artisans to public and private organizations. However, a negative effect was also found in the financing of organizations and family financing.

En México la actividad artesanal está constituida predominantemente por negocios familiares que llevan ya varios años dedicándose a la producción y venta de estos productos. Un rasgo importante en la actividad artesanal es que, al centrarse sólo en la elaboración de las mismas, una gran parte de los artesanos no visualiza el potencial que éstas tienen para su comercialización a través de su exportación a otros mercados. En este sentido, el objetivo de esta investigación es conocer los determinantes de la competitividad medida en la propensión a exportar de los artesanos de la zona lacustre del estado de Michoacán, identificando a la innovación en productos, procesos o marketing, a la afiliación a algún organismo público o privado promotor del desarrollo artesanal, a la intención de los artesanos para posicionarse en nuevos mercados y al financiamiento propio, público/privado o familiar para el desarrollo de las actividades artesanales como variables que influyen de manera positiva en la propensión para exportar productos artesanales por parte de las unidades de producción artesanal de zona del estado de Michoacán. Para alcanzar este objetivo, se aplicaron 329 encuestas entre los artesanos de la zona lacustre del estado de Michoacán. Esta información fue la base para estimar un modelo econométrico de tipo Logit, encontrándose que las variables que tienen un efecto positivo preponderante en la propensión a exportar de las artesanías son la innovación, la intención de los artesanos a posicionarse en nuevos mercados y el financiamiento propio para el desarrollo de actividades artesanales, encontrándose un menor efecto en la afiliación de los artesanos a organismos públicos y privados. Sin embargo, también se encontró un efecto negativo en el financiamiento de organismos y financiamiento familiar.
Instituto de Investigaciones Económicas y Empresariales. Maestría en Ciencias en Negocios Internacionales
Keywords: info:eu-repo/classification/cti/5; ININEE-M-2023-0506; Artesanías; Innovación; Financiamiento; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/16500